El proyecto interdisciplinario: “Privados de Humanidad” - Arce, Christian (2019)
This article aims to present the Interdisciplinary Project in Prison and without Humanity (PPH), an initiative oriented to contribute to the social self-emancipation, not so much from the "scourges" of crime and imprisonment, but from the root causes -and circumstantial ones as well- that have catapulted these two phenomena to be so prominent in our Latin American societies of today. The article seeks to describe a set of interactions between structural-systemic factors, specific elements of political, economic and cultural order, and the awareness of social subjects who live immersed in the phenomena that make up the system of criminality and the prison universe in the Latin America region of the 21st century. The project derived from the application of theoretical and methodological developments of the work of the Rolando García Chair of Humanism, Complexity, and Interdiscipline (CRG) (2015-2017) and the Ibn Khaldun Chair of New Humanism, Hypercomplexity, and Intergnosis (CIJ) (2018-2021). Its purpose was the construction of an interdisciplinary/intergnosis research process on the evolution of the phenomena of criminality and prison universe in the country and throughout the Latin American region. These phenomena occupy a central place in the most severe problems that afflict Costa Rica and Latin America in general, at present.